The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1039/b503501e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the reactions of [FeCl4]– with PhS– or PhSH in MeCN, and the role of cations containing N–H groups

Abstract: The kinetics of the reactions between [FeCl4]- and an excess of PhS- have been studied using stopped-flow spectophotometry. The associated absorbance-time curves can be fitted to two exponentials, and these first and second phases correspond to the formation of [FeCl3(SPh)]- and [FeCl2(SPh)2]-, respectively. It seems likely that the steps involving formation of [FeCl(SPh)3]- and [Fe(SPh)4]- are associated with much smaller changes in absorbance and so are not detected. The kinetics of the first phase exhibit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The studies reported in this paper, together with the studies on: (i) the substitution of ½FeCl 4 À by PhS ) to produce ½Fe(SPh) 4 À (prior to reduction and aggregation to form ½Fe 4 (SPh) 10 2À ) [5], and (ii) reaction [6] of ½Fe 4 ðSPhÞ 10 2À with ½MoS 4 2À to produce ½S 2 Moðl-SÞ 2 Fe(SPh) 2 2À , allow us to sketch out the pathway by which cuboidal clusters containing the fMoFe 3 S 4 g 3þ core framework are constructed. The pathway, which is presumably also followed by other clusters containing fMFe 3 S 4 g nþ cores, is shown in Figure 8.…”
Section: Overall Mechanism Of Cuboidal Cluster Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies reported in this paper, together with the studies on: (i) the substitution of ½FeCl 4 À by PhS ) to produce ½Fe(SPh) 4 À (prior to reduction and aggregation to form ½Fe 4 (SPh) 10 2À ) [5], and (ii) reaction [6] of ½Fe 4 ðSPhÞ 10 2À with ½MoS 4 2À to produce ½S 2 Moðl-SÞ 2 Fe(SPh) 2 2À , allow us to sketch out the pathway by which cuboidal clusters containing the fMoFe 3 S 4 g 3þ core framework are constructed. The pathway, which is presumably also followed by other clusters containing fMFe 3 S 4 g nþ cores, is shown in Figure 8.…”
Section: Overall Mechanism Of Cuboidal Cluster Formationmentioning
confidence: 99%
“…We have already published kinetic and mechanistic studies on systems related to the initial stages in the formation of these cuboidal clusters; namely the substitution reactions of [FeCl 4 À with PhS ) or PhSH [5], and the reaction of ½Fe 4 ðSPhÞ 10 2À with ½MS 4 2À (M=Mo, W or V) [6] to form [S 2 Mðl-SÞ 2 Fe(SPh) 2 2À . In this paper we present the kinetics of the subsequent reactions of ½S 2 Moðl-SÞ 2 Fe(SPh) 2 2À with ½Fe(SPh) 4 2À to form the dicuboidal ½fMoFe 3 S 4 ðSPhÞ 3 g 2 ðl-SPhÞ 3 3À and the reaction of ½ðEtSÞ 2 Feðl-SÞ 2 Vðl-SÞ 2 Fe(SEt) 2 3À with ½Fe(SEt) 4 2À to form the dicuboidal ½fVFe 3 S 4 ðSEtÞ 3 g 2 ðl-SEtÞ 3 3À .…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of PhS À with [FeCl 4 ] À in MeCN, occurs in at least two steps, the first an associative process involving [FeCl 3 SPh] À formation, significant amounts of which may be present at high concentrations of PhS À , followed by rate-determining loss of Cl À . 115 Reactions with PhSH involve initial formation of a solvento complex, [FeCl 3 (CH 3 CN)] followed by rapid substitution by PhSH.…”
Section: Four-coordinationmentioning
confidence: 99%